Managing adverse effects of glaucoma medications - Inoue K (Dove Medical Press, 2014)
Kenji Inoue Inouye Eye Hospital, Tokyo, Japan Abstract: Glaucoma is a chronic, progressive disease in which retinal ganglion cells disappear and subsequent, gradual reductions in the visual field ensues. Glaucoma eye drops have hypotensive effects and like all other medications are associated with adverse effects. Adverse reactions may either result from the main agent or from preservatives used in the drug vehicle. The preservative benzalkonium chloride, is one such compound that causes frequent adverse reactions such as superficial punctate keratitis, corneal erosion, conjunctival allergy, and conjunctival injection. Adverse reactions related to main hypotensive agents have been divided into those affecting the eye and those affecting the entire body. In particular, β-blockers frequently cause systematic adverse reactions, including bradycardia, decrease in blood pressure, irregular pulse and asthma attacks. Prostaglandin analogs have distinctive local adverse reactions, including eyelash bristling/lengthening, eyelid pigmentation, iris pigmentation, and upper eyelid deepening. No systemic adverse reactions have been linked to prostaglandin analog eye drop usage. These adverse reactions may be minimized when they are detected early and prevented by reducing the number of different eye drops used (via fixed combination eye drops), reducing the number of times eye drops are administered, using benzalkonium chloride-free eye drops, using lower concentration eye drops, and providing proper drop instillation training. Additionally, a one-time topical medication can be given to patients to allow observation of any adverse reactions, thereafter the preparation of a topical medication with the fewest known adverse reactions can be prescribed. This does require precise patient monitoring and inquiries about patient symptoms following medication use. Keywords: glaucoma eye drops, adverse reactions, preservatives, main agent